2007
DOI: 10.1152/ajpregu.00248.2007
|View full text |Cite
|
Sign up to set email alerts
|

Localization of ammonia transporter Rhcg1 in mitochondrion-rich cells of yolk sac, gill, and kidney of zebrafish and its ionic strength-dependent expression

Abstract: Members of the Rh glycoprotein family have been shown to be involved in ammonia transport in a variety of species. Here we show that zebrafish Rhcg1, a member of the Rh glycoprotein family, is highly expressed in the yolk sac, gill, and renal tubules. Molecular cloning and characterization indicate that zebrafish Rhcg1 shares 82% sequence identity with the pufferfish ortholog fRhcg1. RT-PCR, combined with in situ hybridization, revealed that Rhcg1 is first expressed in vacuolar-type H(+)-ATPase/mitochondrion-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
128
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 59 publications
9
128
1
Order By: Relevance
“…Control NHE2 expression was also greater in SW trout (Fig.9D); there have been many studies of this apical transporter in various teleosts (reviewed by Ivanis et al, 2008), but the only previous salinity study suggested that expression of NHE2 transiently increased after transfer from brackish water to FW in the killifish (Scott et al, 2005). The lower expression of Rhcg1 in SW (Fig.8C) was consistent with zebrafish larvae exposed to brackish water exhibiting a downregulation of Rhcg1 (Nakada et al, 2007a). To our knowledge, UT expression has not been measured previously in the gills of salmonids subjected to salinity differences, but its greater baseline expression in SW trout (Fig.9I) fits with the general belief that urea-N excretion is more important in marine teleosts (Wood, 1993).…”
Section: Differences In Baseline Gene Expression Between Fw and Sw Troutsupporting
confidence: 67%
See 1 more Smart Citation
“…Control NHE2 expression was also greater in SW trout (Fig.9D); there have been many studies of this apical transporter in various teleosts (reviewed by Ivanis et al, 2008), but the only previous salinity study suggested that expression of NHE2 transiently increased after transfer from brackish water to FW in the killifish (Scott et al, 2005). The lower expression of Rhcg1 in SW (Fig.8C) was consistent with zebrafish larvae exposed to brackish water exhibiting a downregulation of Rhcg1 (Nakada et al, 2007a). To our knowledge, UT expression has not been measured previously in the gills of salmonids subjected to salinity differences, but its greater baseline expression in SW trout (Fig.9I) fits with the general belief that urea-N excretion is more important in marine teleosts (Wood, 1993).…”
Section: Differences In Baseline Gene Expression Between Fw and Sw Troutsupporting
confidence: 67%
“…However, a paradigm shift started 7years ago with the proposal of Weihrauch and co-workers (Weihrauch et al, 2004) that specific channels, the Rhesus (Rh) proteins, were involved in ammonia excretion in crabs. Only in the last 4years has it been realized that these Rh proteins play a crucial role in facilitating ammonia efflux across the gills of fish (Nakada et al, 2007a;Nakada et al, 2007b), especially in the face of high environmental ammonia (HEA) Nawata et al, 2007). A rapid generation of new information has quickly reinforced these initial findings; Wright and Wood (Wright and Wood, 2009) and Weihrauch et al (Weihrauch et al, 2009) provide critical reviews.…”
Section: Introductionmentioning
confidence: 99%
“…HRCs, first described by Lin et al (Lin et al, 2006), express apical H + -ATPase (zatp6v1a) (Lin et al, 2006), NHE3b (zhne3b) (Yan et al, 2007), ammonia conducting rhesus glycoprotein (zrhcg1) (Nakada et al, 2007), CA-15a (zCA15a) (Lin et al, 2008), cytosolic CA2-like a (zCA2 like a) (Lin et al, 2008), basolateral anion exchanger-1b (zslc4a1b) (Lee et al, 2011) and Na + /K + -ATPase subunits atp1a1a.5 and atp1b1b (Liao et al, 2009). Because bafilomycin (a commonly used H + -ATPase inhibitor) inhibits acid secretion at the surface of this cell (Horng et al, 2007;Lin et al, 2006), HRCs are considered to play an important role in acid secretion and Na + uptake coupled to acid secretion .…”
Section: + -Atpasementioning
confidence: 99%
“…The results of recent research underline the importance of the physiological role of the described mechanism, directly conjugated with the basic homeostatic functions of the gill apparatus, ensuring the stability of the parameters of gas exchange, acid-base and osmotic balance of internal environment (Evans et al 2005). However, some authors ascertain the relevance of further research, whose aim is, firstly, the creation of adequate models of clearance of ammonia, which is closely associated with the work of the ion-transporting systems of gill epithelium (Wright and Wood Ch 2009), in-Second, the analysis of physiological and evolutionary aspects of the ways renal clearance of ammonia in fish (Nakada et al 2007), as well as to study the features of neuro-humoral control systems of homeostatic functions of the gill apparatus of fish (Hoshijima and Hirose Sh 2007;Tse et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the study of the effectiveness of glutamatedependent mechanisms intraorganic neutralize the ammonia in some species of fish, a long time can survive in arid environments where the gill system of clearance of nitrogenous products of catabolism are not fully functioning (Anderson et al 2002), promotes the formation of science-based policy in selection of high-value fish species that are resistant to adverse hydrochemical conditions (Wright et al 2007;Sanderson et al 2010). In addition, attract the attention that the fish eggs, along with gill and kidney epithelium, characterized by high expression of specific transport proteins involved in mediated transport of ammonia (Nakada et al 2007). From the position described in this review of the facts, understanding that the fertilized eggs is a powerful incentive not only anabolic potential but also the processes of energy metabolism, we can not exclude that the results of studies of the kinetics of transport of ammonia incubated eggs, may be of interest for the development of biomarkers, targeted for the selection of the most productive producers of fish.…”
Section: Introductionmentioning
confidence: 99%